THE ISSUES AND CHALLENGES OF SHARIAH HARMONIZATION OF THE CROSS BORDER TRANSACTIOINS: CONCEPTUAL REVIEW OF ISLAMIC BANKING INDUSTRIES - Bhuiyan, Abul Bashar; Ali, Md. Jafor; Islam, K. M. Anwarul; Alam, Md. Shahbub; Solaiman, Mohammad (International Journal of Shari'ah and Corporate Governance Research, 2020)
The paper aims to identify major’s regulatory challenges are facing in maintaining proper harmonization of Shariah rulings of Islamic Bank across the world in the cross-border activities. The study found that the Islamic banking is confronting challenges to make appropriate rules and regulations for making the common standardized mode of finance to cope up with present market demand for their customer with conventional counterpart base on the Islamic sharia principles. Particularly, in the arena of competing in the global markets and establish unique regulatory institutions for proper harmonization of Shariah rulings of Islamic Banks over the cosmos in the cross-border actions. The study recommends that policymakers are to pay attention to solve the above regulatory issues to face the existing challenges for the smooth financial operation in the future.JEL Classification Codes: G21, G24, L26, P51.